Melatonin-mediated endogenous nitric oxide coordinately boosts stability through proline and nitrogen metabolism, antioxidant capacity, and Na+/K+ transporters in tomato under NaCl stress - Ghorbani, Abazar; Pishkar, Leila; Saravi, Kobra Valed; Chen, Moxian (Frontiers in Plant Science, 2023)
The interactions between nitric oxide (NO) and melatonin in alleviating sodium chloride (NaCl) toxicity in plants are poorly comprehended. Here, the associations between the exogenous application of melatonin and endogenous NO levels in inducing tomato seedlings' defense response during NaCl toxicity were investigated. The results indicated that the application of melatonin (150 μM) increased height (23.7%) and biomass (32.2%), improved chlorophyll (a (137%) and b (92.8%)), and proline metabolisms, and reduced the contents of superoxide anion radicals (49.6%), hydrogen peroxide (31.4%), malondialdehyde (38%), and electrolyte leakage (32.6%) in 40-day-old tomato seedlings grown under NaCl (150 mM) treatment. Melatonin boosted the antioxidant defense system in NaCl-stressed seedlings by increasing the activity of the antioxidant enzymes. Melatonin also improved N metabolism and endogenous NO content in NaCl-stressed seedlings by upregulating the activity of enzymes implicated in N assimilation. Furthermore, melatonin improved ionic balance and reduced Na content in NaCl-exposed seedlings by upregulating the expression of genes involved in K/Na ratio homeostasis (NHX1-4) and increasing the accumulation of mineral nutrients (P, N, Ca, and Mg). However, the addition of cPTIO (100 μM; an NO scavenger) reversed the beneficial impacts of melatonin, indicating the effective function of NO in melatonin-induced defense mechanisms in NaCl-stressed tomato seedlings. Therefore, our results revealed that melatonin improves the tolerance of tomato plants during NaCl toxicity by mediating internal NO.